An all-inorganic polyoxometalate–polyoxocation chemical garden. Issue 9 (17th December 2015) - Points, Laurie J.; Cooper, Geoffrey J. T.; Dolbecq, Anne; Mialane, Pierre; Cronin, Leroy
Abstract : Wholly inorganic chemical gardens are produced from a cationic polyoxometalate seed in an anionic POM solution which display six concentration dependent growth regimes. Abstract : Herein, we show it is possible to produce wholly inorganic chemical gardens from a cationic polyoxometalate (POM) seed in an anionic POM solution, demonstrating a wholly POM-based chemical garden system that produces architectures over a wide concentration range. Six concentration dependent growth regimes have been discovered and characterized: clouds, membranes, slugs, tubes, jetting and budding.